2016
DOI: 10.3389/fpubh.2016.00038
|View full text |Cite
|
Sign up to set email alerts
|

The Mixed Nature of Incentives for Community Health Workers: Lessons from a Qualitative Study in Two Districts in India

Abstract: Incentives play an important role in motivating community health workers (CHWs). In India, accredited social health activists (ASHAs) are female CHWs who provide a range of services, including those specific to reproductive, maternal, neonatal, child, and adolescent health. Qualitative interviews were conducted with 49 ASHAs and one of their family members (husband, mother-in-law, sister-in-law, or son) from Gurdaspur and Mewat districts to explore the role of family, community, and health system in supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 21 publications
6
37
0
Order By: Relevance
“…In addition to these attributes, CHWs are expected to have other characteristics to better suit them for the role. In general, CHWs providing health services to women and children tend to be female [ 15 , 16 , 18 , 21 , 27 , 37 , 39 , 43 , 52 , 89 92 ] and those providing services in a health facility may be required to have some form of healthcare experience [ 23 , 24 ]. Previous primary or secondary education is sometimes considered in the selection of CHWs [ 24 , 28 , 29 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these attributes, CHWs are expected to have other characteristics to better suit them for the role. In general, CHWs providing health services to women and children tend to be female [ 15 , 16 , 18 , 21 , 27 , 37 , 39 , 43 , 52 , 89 92 ] and those providing services in a health facility may be required to have some form of healthcare experience [ 23 , 24 ]. Previous primary or secondary education is sometimes considered in the selection of CHWs [ 24 , 28 , 29 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…training provided in a health facility by NGOs) [ 4 , 19 , 21 , 43 , 50 , 53 , 91 , 99 , 123 , 124 ]. Individuals with some form of secondary education and subsequent job-related pre-service training outside a recognised training institution lasting any time from a few days to a few weeks [ 35 , 92 ]. Individuals with some form of secondary education and subsequent pre-service training in a recognised training institution lasting a few months to more than a year [ 18 , 26 , 27 , 32 , 39 , 46 , 52 , 68 , 125 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, Scott K. and Shanker S. also reported that ASHAs were limited by the performancebased payments and delayed incentives [16]. Some ASHAs have campaigned to change their payment method to a regular salary-based system rather than the unstable performance-based incentives, but this has not been approved by the NRHM [17]. Differences in the compensation system within states, variability in pregnancy cases within communities, and ability to rely on the incentives provided to ASHAs were not controlled for in this analysis but may all affect the results presented above.…”
Section: Discussionmentioning
confidence: 99%
“…They are often confronted by challenges such as lack of support by supervisors, and insufficient and/or delayed remuneration which impacts their motivation12 and often leads to attrition. While some studies have explored factors which motivate ASHAs (eg, adequate compensation and community recognition),13 14 there is no empirical evidence about the relative importance of the different incentives that may help to retain ASHAs in service.…”
Section: Introductionmentioning
confidence: 99%